Effects of positive psychological interventions on quality of life in patients with first-episode depression - Lv, Lizhao; Han, Keyan; Meng, Limin; Wang, Jincheng; Yin, Hui; Ren, Kenan; Liu, Zhihua (Frontiers in Psychiatry, 2025)
ObjectiveThis study aims to investigate the effects of positive psychological interventions (PPIs) on improving the quality of life in first-episode depression patients.MethodsA total of 200 first-episode depression patients were randomly assigned to a control group (n=100, conventional nursing) or a study group (n=100, conventional care plus four weekly 60–80-minute PPI sessions over one month). Depression severity (Hamilton Depression Rating Scale, HAMD), psychological resilience (Connor-Davidson Resilience Scale, CD-RISC), self-acceptance (Self Acceptance Questionnaire, SAQ), and quality of life (SF-36) were assessed pre-intervention and 3 months post-intervention.ResultsBaseline measures showed no significant intergroup differences (P>0.05). At 3 months, the study group exhibited greater HAMD reduction (Δ=11.16 vs. Δ=9.09 in controls; mean post-intervention: 17.03 ± 3.45 vs. 19.23 ± 3.21, p<0.001), higher CD-RISC improvement (Δ=36.27 vs. Δ=29.54; 80.09 ± 7.86 vs. 73.92 ± 7.36, p<0.001), and increased SAQ total scores (Δ=18.17 vs. Δ=12.25; 43.47 ± 9.21 vs. 37.84 ± 8.24, p<0.001). SF-36 total scores improved by 52.0% in the study group (540.41 ± 32.66 vs. 276.41 ± 27.99) compared to 42.5% in controls (487.85 ± 31.89 vs. 279.48 ± 26.39, p<0.001).ConclusionPPIs delivered over four weeks significantly enhance quality of life and psychological outcomes in first-episode depression, supporting clinical adoption.